Potensi Limbah Cair Karet dan Diapers sebagai Pupuk dengan Fermentor Pumakkal untuk Produktivitas Edamame - Pujaan Tika; Hening Widowati; Agus Sutanto (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to inform the public about the potential utilization of rubber wastewater and disposable diaper waste as raw materials for organic fertilizer using Pumakkal as a fermentor to enhance edamame productivity. The method used was a literature study of relevant scientific sources, including national and international journals, books, and research reports discussing the characteristics of rubber wastewater, the hydrogel content and organic compounds in disposable diapers, the role of indigenous bacteria in Pumakkal during the fermentation process, and the compliance of organic fertilizer with Indonesian National Standard (SNI). The results showed that rubber wastewater still contains organic materials with potential use as fertilizer, while disposable diapers contain hydrogel and organic compounds from urine that can support nutrient availability. Pumakkal fermentor, which contains indigenous bacteria derived from pineapple wastewater, was able to effectively degrade organic materials, resulting in fertilizer that meets SNI quality standards and has the potential to be applied to improve edamame productivity. In conclusion, the utilization of rubber wastewater and disposable diapers with Pumakkal fermentor shows promising potential as an environmentally friendly organic fertilizer and as a sustainable solution for waste management and edamame productivity enhancement. Keywords: Diapers, Liquid Rubber Waste, Pumakkal